1992
DOI: 10.1002/ajmg.1320430126
|View full text |Cite
|
Sign up to set email alerts
|

Recent experience in prenatal diagnosis of fragile X

Abstract: Our experience with 48 prenatal fragile X cases (35 amniocenteses; 13 chorionic villi samplings) is summarized. Of these 48 cases, 18 consultands were known to be carriers of fragile X. No cytogenetic false negatives or positives were identified but 2 cases were uninterpretable. Cytogenetic recommendations include: 1) Ten or more days recovery time after growth in Chang medium, and 2) use of 3-4 media/inducer systems with duplicate harvests. Direct DNA probe testing will likely be the method of choice for pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Treatment is not possible at the present time but accurate prenatal diagnosis and selective termination of affected fetuses can be offered,27 which is the chosen option in some families. 28 A genetic screening programme has some special aspects for consideration. It has been recommended by the World Health Organisation that when a new genetic test becomes available it should first be assessed with the families of affected people.29 A recent working party on screening for fragile X syndrome concluded that screening the general population is neither feasible nor ethical at present, and resources should be concentrated on diagnosing affected children and offering services to their families including DNA testing, genetic counselling, and prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is not possible at the present time but accurate prenatal diagnosis and selective termination of affected fetuses can be offered,27 which is the chosen option in some families. 28 A genetic screening programme has some special aspects for consideration. It has been recommended by the World Health Organisation that when a new genetic test becomes available it should first be assessed with the families of affected people.29 A recent working party on screening for fragile X syndrome concluded that screening the general population is neither feasible nor ethical at present, and resources should be concentrated on diagnosing affected children and offering services to their families including DNA testing, genetic counselling, and prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%